Exploring the Use of Cropping Indices Over the Growth and Yield Performance for Selecting Okra–Cowpea Intercropping Systems - Kirisha, A.; Jeyavanan, K.; Sritharan, S. (Enviro Research Publishers, 2024)
Intercropping of crops has several advantages over monocropping systems, offering efficient utilization of farm resources. While growth and yield remain primary determinants of intercropping success, factors such as crop selection, farm resources, cropping period, and competition also influence outcomes. The choice of appropriate evaluation methods becomes significant for sustainable crop management. Therefore, employing suitable evaluation methods is crucial in the choice of an intercropping system. To address this, three intercropping systems were established in a randomized complete block design (RCBD): single row of okra with single row of cowpea (T1), single row of okra with double–row of cowpea (T2), and double–row of okra with single row of cowpea (T3). Additionally, monocropping systems of each crop were established for evaluation of cropping indices. Cropping indices such as land equivalent ratio (LER), relative yield total (RYT), area time equivalent ratio (ATER), competition index (CI), aggressivity index (Ai) and multiple cropping index (MCI) were applied to assess the intercropping systems. We found that the most favourable combination was T3 based on cropping indices, contrasting with outcomes from growth and yield analysis (T1 and T2). T3 exhibited a yield advantage of 4.2%, with no observed crop competition and maximal land utilization (>95%), establishing cowpea as the dominant crop in these systems. In conclusion, while growth and yield analysis have been practiced in evaluating intercropping systems, this study emphasizes the importance of incorporating cropping indices to comprehensively assess efficiency and sustainability in intercropping practices.
Keywords: Cropping Indices; Growth; Intercropping systems; Okra–cowpea; Yield